15
Step-by-step explanation:
We are given with
a1 = 2
r = 4
These are components of a geometric series. The first term is 2 and the common ratio is 4. To get the first six terms, we use the formula:
an = a1 r^(n-1)
a1 = 2 (4)^(1-1) = 2
a2 = 2 (4)^(2-1) = 8
a3 = 2 (4)^(3-1) = 32
a4 = 2 (4)^(4-1) = 128
a5 = 2 (4)^(5-1) = 512
a6 = 2 (4)^(6-1) = 2048
Step-by-step explanation:
7+2x-2 = 4x -3
5= 2x -3
2x = 8
x = 4
Answer:
you need to bring the 8x over then the -3
Step-by-step explanation:
X^2-3x+27=8x-3
X^2-11x+27=-3
x^2-11x+24
Is that what you are looking for??
Hope that helps feel free to ask more questions
Brainliest??